2018
DOI: 10.3791/57655
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aquatic Biofilms with Flow Cytometry

Abstract: Biofilms are dynamic consortia of microorganism that play a key role in freshwater ecosystems. By changing their community structure, biofilms respond quickly to environmental changes and can be thus used as indicators of water quality. Currently, biofilm assessment is mostly based on integrative and functional endpoints, such as photosynthetic or respiratory activity, which do not provide information on the biofilm community structure. Flow cytometry and computational visualization offer an alternative, sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Although this, and our previous studies have demonstrated the potential of the new methods, more studies are needed to see whether they work equally well in a variety of environmental conditions. We have so far shown that FC-CS can be a good indicator of changes in biofilms under temperature ( Sgier et al, 2016 ) and chemical stress, and that it can be evaluated in a relatively short amount of time once set up ( Sgier et al, 2018 ). However, missing are studies that would measure FC-CS across a gradient of chemical concentration of different chemicals to see what the limits of sensitivity are.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this, and our previous studies have demonstrated the potential of the new methods, more studies are needed to see whether they work equally well in a variety of environmental conditions. We have so far shown that FC-CS can be a good indicator of changes in biofilms under temperature ( Sgier et al, 2016 ) and chemical stress, and that it can be evaluated in a relatively short amount of time once set up ( Sgier et al, 2018 ). However, missing are studies that would measure FC-CS across a gradient of chemical concentration of different chemicals to see what the limits of sensitivity are.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate the interpretation of the viSNE maps and the defined subpopulation, FC data of reference species (16 diatoms, 8 green algae, 6 cyanobacteria, and 1 red algae species, Supplementary Table S6 ) were projected on the viSNE map. For a more detailed description of the procedure, see ( Sgier et al, 2016 , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acid content can vary with environmental conditions. Kelly and Scheibling (2012), Taipale et al (2013), Galloway and Winder (2015), Galloway et al (2015) particle size, particle density, biovolume, pigments, and rough taxonomy at one time (Sgier et al 2018). While the initial calibration and machine training can be time intensive, once mastered, the procedure can lead to fast results.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Culture base techniques used for the analysis of microbiological samples are time consuming; they are not able to detect non-culturable microorganisms and they do not provide real-time information on the physiological status of the organism in situ [9]. FCM is largely used in food industry for optimization and monitoring of microbial industrial processes [10,11], for the detection of microbial contaminants in food products [12] and also it has applications in environmental research [13]. But although in clinical laboratories the application of the flow cytometric technique is well established in hematology and the use of this method in routine clinical microbiology is still rare [14].…”
Section: Fcm Applications In Microbiologymentioning
confidence: 99%